Harnessing the Power of Genomics and Immunoinformatics To Produce Improved Vaccines - Moise, Leonard (2010)
The role of cellular immunity as a mediator of protection against disease is gaining recognition, particularly in regard to the many pathogens for which we presently lack effective vaccines. As a result, there is an ever-increasing need to understand the T cell populations induced by vaccination and therefore T cell epitopes responsible for triggering their activation. Although the characterization and harnessing of cellular immunity for vaccine development is an active area of research interest, the field still needs to rigorously define T cell epitope specificities, above all, on a genomic level. New immunoinformatic epitope mapping tools now make it possible to identify pathogen epitopes and perform comparisons against human and microbial genomic datasets. Such information will help determine whether adaptive immune responses elicited by a vaccine are both pathogen-specific and protective, but not cross-reactive against host or host-associated sequences that could jeopardize self-tolerance and/or human microbiome-host homeostasis. Here, we discuss advances in genomics and vaccine design and their relevance to the development of safer, more effective vaccines.